PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PT. CIPTA MANDIRI WIRASAKTI - Rut Masna Lamminar; Bongsu Saragih (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
To determine the effect of Work Environment and Compensation on Employee Job Satisfaction PT. Cipta Mandiri Wirasakti. This research uses a quantitative approach, namely through the causal type inferential analysis. This research seeks to examine the effect of the independent variable on the dependent variable. In this study the population is the employees of PT. Cipta Mandiri Wirasakti with 440 employees. Based on the Slovin formula, the sample in this study was 82 people. Collecting data in this study using a closed questionnaire. The analysis method used partially and simultaneous linear regression analysis. Based on the results of the analysis, then 1). There is a positive and significant influence between the work environment on employee job satisfaction. 2). There is a positive and significant influence between compensation on employee job satisfaction. 3). There is a significant influence between work environment and compensation on job satisfaction of employees of PT. Cipta Mandiri Wirasakti.